Optimizing Traditional Games as Alternative Physical Activities to Reduce Gadget Dependency Among Children - Purwanta; Anggraini Ihza Rizkita; Hangga Katon Dewantoro (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
The excessive use of gadgets among children has become a serious issue in the KKN-PPM UGM unit JI018, located in Dadi Village and Puntukdoro Village, Plaosan Subdistrict, Magetan Regency, East Java. This problem negatively impacts their physical, psychological, and social development. Children who spend too much time on gawais are at risk of experiencing health issues such as Computer Vision Syndrome (CVS), eye irritation, headaches, and sleep disturbances. Psychologically, excessive gadget use can reduce concentration, increase anxiety, and lead to dependence on digital stimulation. Moreover, gadget use also aﬀects children’s social interactions, where they tend to participate less in social and physical activities. The aim of this study is to optimize traditional games as an alternative physical activity to reduce gadget dependence among children. The study was conducted at SDN Dadi 2, Plaosan Subdistrict, Magetan Regency, involving 6th-grade students as the main respondents. The research method employed was qualitative, involving direct observation, interviews, and training in various traditional games such as "engklek," "gobak sodor," "dakon," hula hoop, and "bekel." The results showed that traditional games successfully attracted students’ interest in being physically active and socially interactive, ultimately reducing their gadget dependence. Students demonstrated high enthusiasm during the training, and their social interactions signiﬁcantly improved during the games. Additionally, the KKN-PPM UGM unit JI018 team handed over several traditional game tools to the school as a follow-up so that these games can continue after the study concludes. This handover aims to encourage students to choose physical activities over excessive gadget use. In conclusion, reducing gadget dependence through eye exercises and non-digital activities such as traditional games is crucial for maintaining children’s physical and mental health, as well as improving their social and motor skills.